Preclinical development and clinical safety assessment of a synthetic peptide conjugate enabling endogenous antibody binding to promote innate receptor engagement - Erika A.K. Fletcher; Robert A. Cordfunke; Aikaterini Nasi; Gunilla Törnqvist; Rob R.P.M. Valentijn; Anna Bergqvist; Marita Westhrin; Wenche Rasch; Frida Lindqvist; Inken Dillmann; Martin Lord; Neanke Bouwman; et al. (Molecular Therapy: Oncology)
Peptide-based vaccines can be used to deliver tumor-specific antigens to dendritic cells (DCs), leading to tumor-directed T cell responses. We previously developed a peptide-peptide conjugate technology enabling in vivo cross-linking of pre-existing tetanus toxin-directed antibodies, facilitating antigen delivery to, and activation of DCs. To achieve this, multiple identical tetanus toxin-derived B cell epitopes (MTTEs) are conjugated to synthetically produce target antigens of choice. Herein, we describe the generation of a prostate cancer vaccine candidate (TENDU) based on this technology. It includes long synthetic peptides harboring epitopes (CD4 and CD8) from prostate-specific antigen (PAP) and prostate-specific membrane antigen (PSMA). The preclinical efficacy of TENDU was assessed in experimental systems, and safety was evaluated in a rabbit toxicity study and a human whole blood loop assay. We also report the first clinical safety assessment of TENDU. Experimental studies showed that prostate cancer patients mounted anti-MTTE antibodies in response to tetanus vaccination with recall T cell responses detected in two patients. Transgenic humanized HLA-DR4 mice displayed T cell responses and increased anti-MTTE IgG levels after vaccination with a peptide construct including an HLA-DR4 epitope. The vaccine candidate was found safe, and a positive correlation between T cell responses and anti-MTTE antibodies was noted in the first-in-human study.